Regional distribution of cytochrome c oxidase activity and copper in sclerotic hippocampi of epilepsy patients. Issue 2 (7th December 2020) - Opačić, Miloš; Ristić, Aleksandar J.; Sokić, Dragoslav; Baščarević, Vladimir; Raičević, Savo; Savić, Slobodan; Zorović, Maja; Živin, Marko; Šelih, Vid Simon; Spasojević, Ivan; Savić, Danijela
Abstract: Introduction: Disruption of copper homeostasis and dysfunction of mitochondria have been documented in sclerotic hippocampi (HS) of patients with mesial temporal lobe epilepsy (mTLE). However, a potential link between these pathological changes has not been tackled so far. Herein, we analyzed regional distribution of neuron somata density, copper concentration, and the activity of cytochrome c oxidase (CCO), a component of mitochondrial electron transport chain and copper‐containing metalloprotein, in HS. Methods: Histochemical staining and laser ablation inductively coupled plasma mass spectrometry were carried out to construct comparable maps of these parameters in coronal sections of hippocampi of 3 mTLE‐HS patients and 3 control subjects. Results: Copper levels were decreased in all regions of HS with pyramidal neuron somata. CCO activity was significantly reduced in stratum pyramidale (PY) 1 and cornu Ammonis field 4, the two regions with significant reduction in neuron somata density. CCO activity was also lower in layers that contain apical dendrites of pyramidal neurons and mossy fibers. It appears that copper deficiency in PY2 and PY3 comes before CCO activity reduction and neuronal loss. A strong positive correlation was found between neuron density, Cu concentration, and CCO activity. Conclusions: Presented results imply that pathological alterations in Cu and energy metabolism could be involved in the development of HS. A limitation of this study was the relatively small number of patients. However, presented results underline copper deficiency as a component of pathological mechanisms of epilepsy and warrant further investigation of cuproproteins and members of copper transport machinery. Abstract : Regional distribution of neuron somata density, copper concentration, and the activity of cytochrome c oxidase in coronal sections of sclerotic hippocampi of epilepsy patients and controls.